Analisis Usability dan Redesain Website Pemerintah Kabupaten Karawang untuk Mendukung Akses Informasi Publik - Dewi, Erika Sita; Kamajengan, Gagas Cahya; Sukarno, Haliza Adzikia; Garno, Garno (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Local government websites play a strategic role as the primary channel for public information, yet many still face usability-related issues. This study aims to measure the usability level of the Karawang Regency Government Website, identify problems encountered by users, and redesign the website interface based on the findings. The evaluation was conducted using a questionnaire based on Nielsen's (1994) usability components, consisting of 9 Likert-scale statements (1–5) and 2 open-ended questions, distributed online via Google Form to 25 respondents. The results showed an overall average score of 2.65, categorized as Sufficient (2.60–3.39), with the main issues identified in cluttered visual layout, confusing navigation, suboptimal mobile responsiveness, irrelevant search results, and lack of information on the service pages. Based on these findings, a selective interface redesign was conducted on five priority areas and implemented as a functional prototype using HTML, CSS, and JavaScript. The results of this study are expected to contribute to improving the quality of public information services on the Karawang Regency Government Website.